Multimodal Cancer Therapy Involving Oncolytic Newcastle Disease Virus, Autologous Immune Cells, and Bi-Specific Antibodies - Schirrmacher, Volker; Fournier, Philippe (Frontiers in Oncology, 2014)
This chapter focusses on oncolytic Newcastle disease virus (NDV). It summarizes i) the peculiarities of this virus as an anti-cancer and immune stimulatory agent and ii) approaches to further harness it as a vector to combat cancer. Special emphasis is given on combining virus therapy with cell therapy and on improving tumor targeting. The review will include some of the authors work on NDV, bispecific antibodies and cell therapy as building blocks for a new perspective of multimodal cancer therapy. The broad anti-tumor immune reactivation includes innate and adaptive, tumor antigen specific and tumor antigen independent activities.